Route of Drug Abuse and Its Impact on Oral Health-Related Quality of Life among Drug Addicts - Aditi Sharma; Simarpreet Singh; Anmol Mathur; Vikram Pal Aggarwal; Neha Gupta; Diljot Kaur Makkar; Manu Batra; Deeksha Gijwani (Addiction and Health, 2018)
Background: Various studies have tested quality of life (QOL) among drug addicts, however very few have reported any association between oral health-related quality of life (OHRQOL) and mode of drug administration among drug addicts. Hence, the present study was conducted aiming to evaluate the impact of mode of administration of drugs on OHRQOL among drug addicts. Methods: Data was collected using respondent-driven sampling (RDS) method among 313 male drug addicts in Sri Ganganagar, Rajasthan, India, using self-administered questionnaires on oral hygiene aids and drug addiction history. OHRQOL was recorded using Oral Health Impact Profile (OHIP-14) questionnaire. The chi-square test, t-test, and Kruskal-Wallis test were used for statistical analysis. Findings: In this study, 56.2% of the drug addicts reported practicing oral hygiene aids. The main drugs abused were heroin, cocaine, and amphetamines as 51.4%, 35.1%, and 13.4%, respectively. Most of the drug addicts were employed (82.4%) and studied up to primary education (46.3%). The highest mean values of community periodontal index (CPI) and decayed, missing, filled surface (DMFS) were found among the cocaine addicts and amphetamine abusers with rates of 3.11 ± 0.98 and 6.69 ± 8.52, respectively. Poor OHRQOL was observed among addicts who consumed drugs in inhalation since a long time irrespective of the type of the drug, but among them heroin addicted subjects had the poorest OHRQOL. Conclusion: OHRQOL was poor among the drug addicts in comparison to general population. Preventive strategies on oral health and other health promotion programs for this vulnerable group can be unified.